Analisis Sistem Informasi Pembebasan PPN Kedutaan Besar dan Organisasi Internasional Dengan Metodologi FAST - Yosinta Suwastika (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The Directorate General of Taxes is intensively implementing Tax Reform chapter 3. The digitization of tax administration is carried out as the realization of one of its pillars; information technology and database. Despite the progress achieved, some taxation services are still held without adequate support of information systems, including VAT exemption for Foreign Representatives and International Organizations. The aims of this research are to dig deeper into the problems which arise in the VAT exemption process for Foreign Representatives and International Organizations as well as to seek solutions to them by implementing Framework for the Application of Systems Thinking (FAST) methodology. This research employs qualitative method with a case study approach conducted at the DGT. The data collection was conducted through observation, document analysis, and interviews with the DGT’s employees involved in the process. This research shows that without the support of an integrated information system, the VAT exemption process for Foreign Representatives and International Organizations does not run effectively and efficiently. This research resulted in logical designs and web-based information system prototypes applicable to solve the problems in the VAT exemption process for Foreign Representatives and International Organizations.